Evaluative Process Base on Conceptual Problem Based Learning Model : A Conceptual Framework for Learning Tools to Train Critical Thinking - Herdiyana Fitriani; Taufik Samsuri; Fida Rachmadiarti; Raharjo Raharjo (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Critical thinking has important applications in every area of life and learning and is allegedly the main theme and goal of achieving competence in learning. Critical thinking can be taught through learner-centered interactive learning using learning tools that are relevant to the attributions of achievement of critical thinking skills. This study aims to develop a conceptual framework for evaluative-process learning tools based on conceptual-problem-based learning models to train students' critical thinking. The conceptual framework in question is a hypothetical evaluative-process framework based on the CPBL model, this is supported by the accompanying textbook mode. This study is a preliminary research (develop preliminary form of product). The product in question is an evaluative-process tool based on the CPBL model to train students' critical thinking. In accordance with the objectives of this study, the hypothetical framework was developed based on: a) research and information collecting; and b) planning. Research and information collecting is based on several aspects that have been carried out by researchers, namely a review of literature, classroom observation, and preparation of a state-of-the-art report. While in the planning process, defining skills and stating objectives determining course sequence have been carried out, where in the study conducted, critical thinking skills have been determined as the main aspect of the objectives of development, and the CPBL model has been determined as the basis model in the development of evaluative-process tools. The focus in this study covers two main aspects, namely developing a hypothetical evaluative-process framework based on the CPBL model and developing a textbook framework as an evaluative-process supporting tool based on the CPBL model.